Identifying the Effects of Mergers and Acquisitions on Turkish Banks Performances - Küçükkocaoğlu, Güray; Bozkurt, Melike Aktaş (Asian Journal of Economic Modelling, 2018)
Globalization has opened more capital pools of financing in emerging markets where foreign banks can now consider and engage in partnerships, mergers and acquisitions. Banks, the backbone of the financial system, intervene with mergers and acquisitions at a higher rate to better meet the considerations of the industry and the competition. All around the emerging markets, the financial sector has been carrying out acquisitions of private banks, especially in Turkey, where the post-crisis restructuring efforts include merger and acquisition opportunities and strategies for the Turkish Banking Sector. This paper aims to find the effects of mergers, acquisitions and share transfers on the performances of the Turkish Banks between 2001-2012. The Probit Model has been used to identify the performance changes of nine banks that were subject to merger and acquisition. Seven independent variables of Capital Adequacy Ratio, Fixed Assets / Total Assets, Financial Assets / Total Assets, Interest Income / Total Assets, Liquid Assets / Short-term Liabilities, Net Profit / ROA, Net Profit / ROE were used. Based on the analysis, three of the ratios: Fixed Assets / Total Assets, Interest Income / Total Assets, Liquid Assets / Short Term Liabilities decreased following the merger/acquisition in Turkish banks’ financials after the merger/acquisition activity of a foreign bank.